[Students in Yosemite Hall dorm room] (1977)
Three students sitting in various ways, one on a desk, another on a bed, and another on a chair engage in conversation while one smiles, under a poster of a dirtbike with the phrase 'Do it in the Dirt'. A Disneyland pennant hanging from the wall as well as other posters decorate closets while speakers and a fan are sitting above them. Also in the room is a clock radio and a chess board with the pieces set up on it.